Anisotropy Of Magnetic Susceptibility Analysis In Cores Of Tunas Formation (Permian), Claromecó Basin, Buenos Aires, Argentina: It Relation With Depositional Conditions - Febbo, María Belén (2019)
Claromecó Basin (Buenos Aires Province, Argentina) is composed by carboniferous-permian rocks that lie on a Paleozoic basement. The PANG 0003 well, located in the center of the basin, contains rocks from the Tunas Formation. The succession is composed by sandstone, mudrock, carbonaceous mudrock, coal and tuff. The aim of this work is to analyze the internal structure of cores through anisotropy of magnetic susceptibility (AMS) studies and to relate these parameters with depositional and post-depositional conditions. Additionally, the aim is to compare the results with previous outcrop data of the Tunas Formation. Standard AMS study was carried out from the base to the top of the well. AMS parameters vary with depth. Magnetic susceptibility (Kmean) presents an average of 209 x10-6 SI, consistent with the presence of paramagnetic minerals. Anisotropy degree (Pj) values increase with depth due to overburden. The shape parameter (T) mainly range from 0 < T < 1 indicating oblate fabric. As the cores are not oriented, Kmax axis lie distributed in the Equatorial plane, near the horizontal, while Kmin axis position are near the vertical, perpendicular to the bedding plane, with horizontal attitude indicating a triaxial to sedimentary fabric. These results are consistent with those obtained from the outcrops that indicate efforts attenuating upwards of the sequence and toward the foreland basin located to the east. This kind of study allows increasing the knowledge about the basins as Claromecó, currently considered as frontier basin.